2002
DOI: 10.1046/j.1464-410x.2002.03011.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturia in the Dutch adult population

Abstract: Objective To estimate the prevalence of nocturia in the Dutch adult population, its association with sociodemographic and health characteristics, and to assess problems experienced by persons with nocturia. Subjects and methods In spring 2001 a telephone survey was conducted among a representative sample of 4721 Dutch respondents (response 53%). Using questions from the Bristol Lower Urinary Tract Symptoms questionnaire respondents were asked about having nocturia and the problems they experienced. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
3
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 21 publications
12
65
3
1
Order By: Relevance
“…Factors previously reported to be related to nocturia included BMI, hysterectomy, post-menopausal age, 5 caffeine consumption, 25 and factors such as hypertension, poor health status, and the use of medication. 36,37 The findings of this study are consistent with the findings in previous work that nocturia is associated with age. 36,37 In this study, the prevalence rates of nocturia increased with increasing daily caffeine consumption.…”
Section: Storage Symptomssupporting
confidence: 92%
See 1 more Smart Citation
“…Factors previously reported to be related to nocturia included BMI, hysterectomy, post-menopausal age, 5 caffeine consumption, 25 and factors such as hypertension, poor health status, and the use of medication. 36,37 The findings of this study are consistent with the findings in previous work that nocturia is associated with age. 36,37 In this study, the prevalence rates of nocturia increased with increasing daily caffeine consumption.…”
Section: Storage Symptomssupporting
confidence: 92%
“…36,37 The findings of this study are consistent with the findings in previous work that nocturia is associated with age. 36,37 In this study, the prevalence rates of nocturia increased with increasing daily caffeine consumption. However, the prevalence of nocturia for teachers who did not consume caffeine was also high (n ¼ 38, 20.5%).…”
Section: Storage Symptomssupporting
confidence: 92%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]78,79 Many cross-sectional studies after the millennium have shown an independent association of older age with nocturia after multivariate analysis.…”
Section: Agingmentioning
confidence: 99%
“…With regard to sex difference, there are three different findings for the prevalence of nocturia: (i) it is equal in both sexes; 14,17,20,21,26,79 (ii) it is higher in women; 15,22,23,33 and (iii) it is higher in men. 13,16,27 Tikkinen et al reported that women younger than 50 years had more nocturia than men of the same age, but that the prevalence of nocturia increased twice as rapidly in men as among women with aging.…”
Section: Sexmentioning
confidence: 99%
See 1 more Smart Citation